1978
DOI: 10.1002/1520-6629(197810)6:4<328::aid-jcop2290060409>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of a juvenile court volunteer program

Abstract: A longitudinal study of the impact of three separate volunteer programs working with juvenile delinquents was undertaken at one juvenile court. The youth were followed for a period of one year with measures of official and unofficial delinquent behavior obtained four times during that year. Other data were also collected. The study results indicated two of the programs (i.e., volunteer probation officer and group counseling) had a negligible effect on reducing probationers' delinquent behavior compared to a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…), Social Competence Training (26 weekly lessons include stress management, self-esteem, etc)., Family Activities (monthly weekend events for youth, their families, and their mentors). Barnoski (2002) Meet monthly during last 5-6 months of youth confinement in Juvenile facility None Berger & Gold (1978) One on one similar to Big Brothers/Big Sisters Some (number not specified) chose to participate in group counseling or tutoring. Carswell (2002) Group mentoring session 4-5 days/week after school.…”
Section: -16 Yearsmentioning
confidence: 99%
“…), Social Competence Training (26 weekly lessons include stress management, self-esteem, etc)., Family Activities (monthly weekend events for youth, their families, and their mentors). Barnoski (2002) Meet monthly during last 5-6 months of youth confinement in Juvenile facility None Berger & Gold (1978) One on one similar to Big Brothers/Big Sisters Some (number not specified) chose to participate in group counseling or tutoring. Carswell (2002) Group mentoring session 4-5 days/week after school.…”
Section: -16 Yearsmentioning
confidence: 99%
“…The results indicated that youth who had assigned mentors had lower felony recidivism rates over 12 months than youth in a matched group who did not receive mentoring (Barnoski, 1998). Additional studies have also found that mentoring programs reduce recidivism in known juvenile offenders (Berger and Gold, 1978;Hanlon et al, 2002). Connecting known juvenile burglars to mentors could be an effective early intervention tool to prevent the development of burglary expertise among young offenders.…”
Section: The Importance Of Early Interventionmentioning
confidence: 99%
“…There seems to be general agreement that diversion services should be provided on a consensual basis and that pressure on youth to participate in diversion programs by agents of the juvenile justice system limits the effectiveness of such programming (Mullen, n.d.;Berger, 1975). Gibbons and Blake (n.d .…”
Section: As Noncoercivementioning
confidence: 99%